Small molecules inhibit STAT3 activation, autophagy, and cancer cell anchorage-independent growth. Issue 12 (15th June 2017) - Zhou, Donghui; Springer, Maya Z.; Xu, David; Liu, Degang; Hudmon, Andy; Macleod, Kay F.; Meroueh, Samy O.
Graphical abstract: Abstract: Triple-negative breast cancers (TNBCs) lack the signature targets of other breast tumors, such as HER2, estrogen receptor, and progesterone receptor. These aggressive basal-like tumors are driven by a complex array of signaling pathways that are activated by multiple driver mutations. Here we report the discovery of6 (KIN-281), a small molecule that inhibits multiple kinases including maternal leucine zipper kinase (MELK) and the non-receptor tyrosine kinase bone marrow X-linked (BMX) with single-digit micromolar IC50 s. Several derivatives of6 were synthesized to gain insight into the binding mode of the compound to the ATP binding pocket. Compound6 was tested for its effect on anchorage-dependent and independent growth of MDA-MB-231 and MDA-MB-468 breast cancer cells. The effect of6 on BMX prompted us to evaluate its effect on STAT3 phosphorylation and DNA binding. The compound's inhibition of cell growth led to measurements of survivin, Bcl-XL, p21 WAF1/CIP1, and cyclin A2 levels. Finally, LC3B-II levels were quantified following treatment of cells with6 to determine whether the compound affected autophagy, a process that is known to be activated by STAT3. Compound6 provides a starting point for the development of small molecules with polypharmacology that can suppress TNBC growth and metastasis.